Some physiological and chemical properties of horse and cow blood samples under effect of some different types of anticoagulants - Ismail, Muna M.; I. Ali, Hiba; S.Najm, Ikbal; Y. Khadier, Nooralden; M. Rasheed, Yasin; A. Jasim, Riyam; Kh. Khalil , Zakia (The Iraqi Journal of Veterinary Medicine, 2018)
The purpose of the present study is to determine and compare the anticoagulants, Ethylene diamine tetra acetic acid, Sodium oxalate, Sodium citrate and heparin in blood samples of horse and bull, through estimation of (Hemoglobin, Packed Cell Volume and Plasma Platelets Count) and plasma physical properties (clarity and volume) and some chemical properties (pH and calcium ion concentration). Five Blood samples were obtained from five stallions and five bulls (20 ml/sample) and were divided as 5 ml in four test tubes containing Ethylene diamine tetra acetic acid, sodium oxalate, sodium citrate and heparin at the College of Veterinary Medicine, University of Diyala. Hemoglobin and packed cell volume were estimated immediately and then the blood samples were centrifuged for 15 min. at 3000 rpm to obtain plasma for evaluating the physical and chemical properties specified above. The horse blood samples pertaining data had no significant elevation in hemoglobin concentration and packed cell volume in Ethylene diamine tetra acetic acid group as compared to other groups, beside having no significant changes in pH between the four treated groups while there was a significant increase in plasma volume of oxalate and citrate as compared to Ethylene diamine tetra acetic acid and heparin, and there was a significant increase in plasma platelet count of Ethylene diamine tetra acetic acid group as compared to heparin. As well there was a significant decrease of calcium ion concentration in Ethylene diamine tetra acetic acid, oxalate and citrate as compared to heparin, while the results of bull blood samples revealed that the hemoglobin and Packed Cell Volume were significantly higher in heparin group than in the oxalate and citrate groups with non significant differences with Ethylene diamine tetra acetic acid group. The plasma obtained from different types of anticoagulants appeared with a high degree of clarity, and the volume of plasma had no significant increase in oxalate and citrate group as compared to other groups. The Plasma Platelet Count and calcium concentration significantly increased in heparin group as compared to other groups. In conclusion, the Ethylene diamine tetra acetic acid was more reliable for horse blood samples while the anticoagulant heparin was more reliable anticoagulant for bull blood samples.